Exploring the association between secondhand smoke exposure and hearing loss among U.S. nonsmokers - Aashish Batheja; Daniel H. Coelho (PLoS ONE, 2025)
Objective Secondhand smoke (SHS) exposure has been implicated as a risk factor for hearing loss. However, there is a relative paucity of inconsistent findings with limited frequency-specific details. The goal of this study is to better characterize the relationship between SHS exposure and hearing loss among adult nonsmokers in the U.S. Study design Cross-sectional. Setting 2015-2016 NHANES cycle. Patients 1644 nonsmokers between ages 20 and 69 and without diabetes, stroke, or heart disease. Intervention Serum cotinine level (ng/ml) indicated SHS exposure. Main outcome measures Outcomes were hearing thresholds at low-frequencies and high-frequencies as well as hearing loss defined by hearing threshold 20 dB in the better ear. Linear regressions between hearing thresholds and SHS exposure stratified by Body Mass Index (BMI) category and controlled for socio-demographic variables. Logistic regression modeling hearing loss by SHS exposure controlled for the same. Results SHS exposure was associated with elevated hearing thresholds at low-frequencies (β = 0.47, p = .03) only in the obese (BMI 30) population. SHS exposure was associated with greater odds of hearing loss (Odds Ratio: 1.17, 95% Confidence Interval: 1.06–1.29, p = .005) and demonstrated a dose-response relationship. Conclusion While SHS exposure was associated with hearing loss and showed a dose-response relationship, its relationship with hearing thresholds was not demonstrated across all hearing frequencies or BMI categories. Additional research is needed to establish the clinical significance of these findings and clarify the role of obesity in this relationship.